A 2002 National Social Accounting Matrix (SAM) for Peru and Sub-national Matrices for the Coastal and Sierra/Selva Regions - Nin-Pratt, Alejandro; Thurlow, James; Morley, Samuel (International Food Policy Research Institute, 2011)
What is a Social Accounting Matrix (SAM)? (PDF 125K) This is a full regional SAM for the year 2002 and was developed as an input to a regional CGE model developed to analyze regional development strategies. The country was divided into three regions, Costa, Sierra, and Selva. The regional disaggregation relied on a nine sector estimate of regional production from the Peruvian Census Bureau (INEI) regional tax and expenditure date r eported by the Peruvian Ministry of Finance and the United National Development Program. We used regional employment data to estimate sectoral production levels by region at a greater level of disaggregation than the nine sectors reported in the INEI data. The same household surveys gave us an estimate of household saving and consumption by sector and region.